Prevalence of dynamic magnetic resonance imaging-identified pelvic organ prolapse in pre- and postmenopausal women without clinically evident pelvic organ descent. (November 2016) - Cimsit, Canan; Yoldemir, Tevfik; Akpinar, Ihsan Nuri
Background: Dynamic magnetic resonance imaging (dMRI) is an imaging tool that can be used to evaluate and stage pelvic organ prolapse (POP). Greater understanding of the incidental detection of POP in asymptomatic patients is needed. Purpose: To evaluate the prevalence of dMRI-detected POP in pre-and postmenopausal women who were imaged for reasons unrelated to pelvic floor dysfunction. Material and Methods: A total of 227 women who had diagnoses that did not include POP underwent abdominal/pelvic dMRI. Patients with a positive gynecological examination for or a clinical history of POP ( n  = 11), hysterectomy ( n  = 4), or gynecologic-oncology surgery ( n  = 2) were excluded, as well as patients who were unable to strain during MRI ( n  = 11). A total of 199 patients without visible prolapse were enrolled in the study. An H-line, M-line, pubococcygeal line (PCL), and mid-pubic line (MPL) were used to detect and grade prolapse. Results: The prevalence of dMRI-identified POP was higher in postmenopausal subjects. The PCL led to a greater frequency of prolapse detection than the MPL. The frequency of middle compartment descent was similar regardless of whether the PCL or MPL was used as a reference line. There was a higher incidence of prolapse in the posterior compartment. Using an H-line and PCL as references, the anterior and posterior compartments were found to significantly differ between pre- and postmenopausal subjects. The MRI parameters that were used to define POP were not correlated with parity, vaginal birth, BMI, or fetal birth weight. With respect to the MPL, age was correlated with both the presence of an elongated H-line and with descent. Conclusion: Dynamic MRI identified incidental pelvic organ prolapse in asymptomatic patients. The prevalence of dMRI-detected POP was higher in postmenopausal women without visible prolapse. These findings suggest the need for further studies to identify how to modify the currently used dMRI thresholds for postmenopausal women.